JUVENILE OFFENDERS AND VICTIMS OF DIGITAL VIOLENCE - Slađana Jovanović; Ljubinka Marković (Revija za kriminologiju i krivično pravo, 2023)
The authors are focused on the issue of digital violence among juveniles: factors, main characteristics, and responses to it. The paper is primarily based on the latest research results of judicial practice (of the Higher Court in Belgrade and the Higher Prosecution Office in Belgrade – Special Department for High-Tech Crime), data gathered by questionnaires filled out by juveniles from one secondary school in Belgrade, and other available studies on the topic. Some recommendations regarding the social response to digital violence among juveniles were made, having in mind General Comment No. 25 (2021) on children’s rights in relation to the digital environment adopted by the Committee on the Rights of the Child.